PENGARUH JUS SEMANGKA TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS NANGGALO - Nurleny Nurleny (Jurnal Akademika Baiturrahim Jambi, 2019)
Hypertension is a condition in which the blood vessels are high (systolic blood pressure ≥140 mmHg and diastolic ≥90 mmHg) persistent. Statistics are 24.7% of Southeast Asia and 23.3% of Indonesians aged 18 and over are hypertensive by 2014. Hypertension Can be minimized by using pharmacology and nonpharmacology therapy, one of which is watermelon juice.The purpose of this study was to determine the effect of watermelon juice on the decrease in blood pressure of hypertensive patients in the work area of Nanggalo Public Health Center. This type of research is Quasi Eksperimen with one group pretest-posttest design. The researcher data was collected on May 2017 in the working area of puskesmas sijunjung with 15 samples taken from purposive sampling technique. Data were analyzed by paired sample t-test. The results of this study obtained p value = 0.00 (p <0.05) indicates that there is a decrease in blood pressure before and after watermelon juice given. So it can be concluded there is the influence of watermelon juice to decrease blood pressure of hypertensive patients in the work area of puskesmas sijunjung sijunjung district. It is expected hypertensive patients to be able to take advantage of watermelon juice as nonfarmakologi therapy to lower blood pressure. From the results of this study can be concluded that watermelon juice can lower blood pressure hypertensive patients, it is hoped hypertensive patients to be able to take advantage of watermelon juice as nonfarmakologi therapy to lower blood pressure.